The Decision to Wear a Face Mask as a Protective Behavioral Measure Against COVID-19: Survey Results From Greater Kampala Metropolitan Area, Uganda - Bukuluki, Paul M.; Kisaakye, Peter (Frontiers in Public Health, 2021)
The use of face masks is one of the behavioral measures used to prevent COVID-19 infection. Despite the positive contribution of face masks, there is uncertainty surrounding face mask wearing in low-income countries. Using data from 1054 respondents in Greater Kampala Metropolitan area, we investigate the variation in face mask wearing inside and outside public spaces. Results indicate that more than three quarters of the respondents wore a face mask always outside public spaces and slightly more than half wore a face mask sometimes inside public spaces. Respondents who wore masks sometimes (OR=16.8; CI=8.2-34.5) and always (OR=36.0; CI=14.3-90.8) inside public spaces were more likely to wear a face mask to prevent COVID-19 infection. Respondents who wore a face mask outside public spaces sometimes (OR=4.1; CI=1.6-10.3) or always (OR=15.7; CI=6.9-35.7) were more likely to wear a face mask to prevent COVID-19 infection. Respondents who wore a face mask inside public spaces sometimes (OR=15.9; CI=7.1-35.9) or always (OR=6.3; CI=3.0-13.3) were more likely to wear a face mask to prevent COVID-19 infection. Respondents who wore a face mask outside public spaces sometimes (OR=2.3; CI=1.0-5.6) or always (OR=14.4; CI=6.5-31.3) were more likely to wear a face mask to prevent COVID-19 infection than their counterparts who never wore a face mask. There is need to raise awareness about face mask wearing and its efficacy to prevent COVID-19 infection.